2004
DOI: 10.1101/gad.1194004
|View full text |Cite
|
Sign up to set email alerts
|

Loss of C. elegans BBS-7 and BBS-8 protein function results in cilia defects and compromised intraflagellar transport

Abstract: Bardet-Biedl syndrome (BBS) is a genetically heterogeneous developmental disorder whose molecular basis is largely unknown. Here, we show that mutations in the Caenorhabditis elegans bbs-7 and bbs-8 genes cause structural and functional defects in cilia. C. elegans BBS proteins localize predominantly at the base of cilia, and like proteins involved in intraflagellar transport (IFT), a process necessary for cilia biogenesis and maintenance, move bidirectionally along the ciliary axoneme. Importantly, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
322
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 313 publications
(344 citation statements)
references
References 43 publications
17
322
0
2
Order By: Relevance
“…Here, we used a model organism, C. elegans. In C. elegans, 60 of the 302 neurons of the hermaphrodite are ciliated sensory neurons, and several works have demonstrated that the mutants of IFT-related genes show defects in sensory functions (Cole et al 1998;Signor et al 1999;Qin et al 2001;Haycraft et al 2003;Schafer et al 2003;Blacque et al 2004;Scholey et al 2004;Snow et al 2004;Ou et al 2005;Bell et al 2006;Evans et al 2006). In the present work, we identified nematode IFT-81 and IFT-74, whose C. reinhardtii orthologues were recently shown to form core complex in subcomplex B (Lucker et al 2005), and attempted to elucidate their physiological roles in C. elegans.…”
Section: Introductionmentioning
confidence: 96%
“…Here, we used a model organism, C. elegans. In C. elegans, 60 of the 302 neurons of the hermaphrodite are ciliated sensory neurons, and several works have demonstrated that the mutants of IFT-related genes show defects in sensory functions (Cole et al 1998;Signor et al 1999;Qin et al 2001;Haycraft et al 2003;Schafer et al 2003;Blacque et al 2004;Scholey et al 2004;Snow et al 2004;Ou et al 2005;Bell et al 2006;Evans et al 2006). In the present work, we identified nematode IFT-81 and IFT-74, whose C. reinhardtii orthologues were recently shown to form core complex in subcomplex B (Lucker et al 2005), and attempted to elucidate their physiological roles in C. elegans.…”
Section: Introductionmentioning
confidence: 96%
“…Outer dynein arms (ODAs) are also likely cargoes for IFT via interaction with IFT46 through the adaptor protein ODA16 (Hou et al , 2007; Ahmed et al , 2008). Several subunits of the BBSome, a cargo adapter for membrane proteins, have also been demonstrated to move by IFT (Blacque et al , 2004; Lechtreck et al , 2009a) as have several integral and associated membrane proteins (Qin et al , 2005; Huang et al , 2007). …”
Section: Introductionmentioning
confidence: 99%
“…94 Surprisingly, the worm BBS7 homologue moves bidirectionally along the ciliary axoneme and is required for the assembly/function of IFT particles, implicating BBS7 in intraflagellar transport. 100 One of the more interesting ideas to emerge from studies of the BBS proteins in Chlamydomonas, C. elegans, mouse, and humans is that those that associate with centrioles may play roles both in ciliary assembly/function and in cell division. In their centriolar role as basal bodies, they influence cilia function, and in their centriolar role in centrosomes, they influence cell division.…”
Section: Cilia and The Obesity Disorder Bardet-biedl Syndromementioning
confidence: 99%